PLASTIC VESSEL IN THE SHAPE OF A MALE AFRICAN HEAD FROM OLBIA PONTICA - Zhuravlev, Denis; Khmelevskiy, Dmitriy (Rei Cretariae Romanae Fautorum Acta, 2022)
A plastic vessel in the shape of a male African head found during the excavation in Olbia Pontica in 2016 is described in the article. This vessel dates to the 2nd-3rd century AD and was probably used for the transportation of perfume.